A right to be forgotten for cancer survivors: A legal development expected to reflect the medical progress in the fight against cancer. (September 2020) - Scocca, Grazia; Meunier, Françoise
Highlights: In Europe there are more than 12 million cancer survivors. Financial toxicity and denied access to mortgages, loans or life insurances are the most neglected issues for cancer survivors. The Right to Be Forgotten is a legal provision that promotes equality, currently implemented in France Belgium and Luxembourg. Political and legal measures are needed to tackle discrimination and promote social inclusion, at national and at European level. Abstract: The aim of the article is to draw attention about cancer survivors and the challenging obstacles to tackle, once the cure is declared. In particular, one of the most neglected issues for cancer survivors concerns the financial toxicity and specifically the possibility to get access to mortgages, loans or life insurances. The issue concerns more than 12 million cancer survivors in Europe. The practices of creditworthiness assessments are mostly self-regulated by private actors, including the collection and the evaluation of health information and data related to the applicant. In 2016, France adopted a law on the Right to Be Forgotten in this purpose. The same initiative has been implemented later on by Belgium and Luxembourg. The article analyses the content of these legislative initiatives, to disseminate their objectives and promote further perspectives of development to avoid any risk of discrimination for cancer survivors throughout EU. The goal of this study is to promote political solutions, taking into consideration the progress of Medicine and the implementation of legal principles and social values. The article will also provide the opportunity to spread the debate about the social needs of cancer survivors, highlighting the attention about the necessity to provide them with a specific status in the national and European policies, avoiding discrimination and financial toxicity. The study is part of a broader investigation on the right to be forgotten into the EU Area, still ongoing. For this article, the analysis is limited to the three EU Member States that recently adopted a specific legal framework on the issue, underlying the importance to regulate this aspect marked by the increasing success of therapies of cancers.